2015
DOI: 10.1016/j.mimet.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of Mycoplasma hyorhinis using multiple-locus variable number tandem repeat analysis

Abstract: Mycoplasma hyorhinis (M. hyorhinis) has re-emerged as an important swine pathogen in recent years causing significant economic losses in post weaning pigs. Genetic variability of M. hyorhinis has been described based on different molecular methods that have limited resolution and reproducibility. The present study was undertaken to develop a molecular epidemiological typing tool for M. hyorhinis based on multiple loci of variable number of tandem repeats in its genome, termed MLVA. The typing method was design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…No correlation between STs and the age of the pig, year of isolation, sample type, pathogenicity, and state of US origin was observed. These observations are in accordance with others [22,41]. However, in this study three distinct clonal complexes, two of which included strains from the US and one that exclusively contained strains from Mexico, were identified.…”
Section: Discussionsupporting
confidence: 93%
“…No correlation between STs and the age of the pig, year of isolation, sample type, pathogenicity, and state of US origin was observed. These observations are in accordance with others [22,41]. However, in this study three distinct clonal complexes, two of which included strains from the US and one that exclusively contained strains from Mexico, were identified.…”
Section: Discussionsupporting
confidence: 93%
“…MLST and multilocus variable-number tandem-repeat analysis (MLVA) techniques have been developed for M. hyorhinis genotyping ( 25 , 26 ). Genotyping studies have indicated that M. hyorhinis strains exhibit a high degree of diversity between areas and farms, and even within a single farm ( 25 , 27 ). Unfortunately, no connection has been identified yet between any genotype and the virulence characteristics of strains ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…To obtain reliable results only validated methods should be used. Several variants of qPCR techniques have been described so far for the investigation of cell culture contamination caused by Mollicutes [ 1 , 10 , 11 , 31 ].…”
Section: Discussionmentioning
confidence: 99%